이선관 시의 특징과 지향 - 김문주(Kim, Mun-joo) (한국시학연구, 2022)
이선관(1942∼2005)은 40여년의 창작 기간 동안 12권의 시집을 간행하였으며 평생 마산 지역에서 활동한 시인이다. 그는 출생한 해에 질병으로 지체장애 2급 판정을 받았는데, 질병의 후유증으로 몸을 제대로 가누지 못하고 말이 어눌한 상태로 시 창작에 전념하였다. 간명한 언어, 언술의 다양한 변주를 통한 의미의 재생산, 내포의 확대, 언어에 대한 다양한 유희의 감각 등, 그의 시는 말의 내포를 최대한 반추하게 함으로써 현실 비판의 기능을 수행하였다. 특히 1970년대 마산의 지역 현실을 바탕으로 환경과 생태에 대한 문제의식을 선구적으로 제기하였으며, 그것의 연장으로 한반도의 통일과 평화의 문제를 줄곧 시적으로 형상화하였다. ‘이선관’은 1970년대와 1980년대 지역문화 운동의 중요한 이정표였으며, 사후에는 그를 기리는 ‘이선관추모기념사업회’를 통해 지역문화 운동의 거점이 되고 있다. 한국 생태문학의 선구적인 업적을 보여주고 있음에도 불구하고 그에 대한 연구 성과는 미미한 편이다. 이 논문에서는 이선관의 시를 둘러싼 문제적인 지점들을 점검하고, 그의 시세계의 특징을 시론 격에 해당하는 「시는」이라는 작품을 분석함으로써 정리하였다. 그에게 시는 인간의 의지와 뜻을 올곧게 표명하고, 생명에의 환희와 인간의 자존(自存)을 표현하는 장(場)이었으며, 궁극적으로 그의 시는 화해와 평화를 향한 도정이었다. 이선관의 시는 우리에게 말의 생생한 생명력과 기능을 재삼 반추하게 하는 세계이다. 육체적 장애로 인해 말을 원활하게 구사하기 어려웠던 이선관의 시는 오히려 말의 원초적 생명력과 역능(力能)을 사유하게 하는 장(場)이다. 평생을 ‘마산’에서 활동하면서 지역의 문제에 기반하여, 환경과 생태 나아가 통일과 평화의 문제를 선구적으로 시화하였던 이선관을 한국현대시사는 진지하게 검토할 필요가 있다. Lee Seon Gwan(1942~2005) is a poet from Masan who published 12 collections of peoms during his 40 years of creative activity. In the year of birth, he was diagnosed with class-2 physical disability by disease. Therefore he was unable to control himself and inarticulate in his speech, but devoted his life in poetic writing. His poems criticized reality by having people ruminate on the connotaion of words. They feature reproduction of meaning with the clear language variations of speech, maximization of connotation, and various senses of play on words, etc. He brougt up the problem of environment and ecology in particular based on issue in Masan of 1970s. By extention, he continually poeticized poeunification of Korean Peninsula and issue of peace. Lee Seon Gwan was an important milestone of local cultural movement in 1970s and 1980s. and ‘Lee Seon Gwan Memorial Foundation’ has become a base of it after his death. Although his works showed us pioneering achievements of ecological literature, there are few research on him. In this thesis, I check the problematic points of Lee Seon Gwan’s poems, summarize his characteristic of poetic worlds by analyzing the work of 「the Poem is」 which can be shown as ‘poetics’. For him, a peom was a place where he expressed a will of human, joy of life and self-respect of human. Ultimately, his peotic work was a path toward reconciliation and peace. Lee Seon Gwan’s poems make us ruminate on vitality of language and its funtion. Poem written by Lee Seon Gwan who were unable to speack fluently due to physical disability is a great filed that have people think about original viltality and potentia of words. In hisotory of modern Korean poetry, there is a need to seriously look Lee Seon Gwan who devoted all his life in Masan playing a leading role in poeticizing local issues of ecology and environment, by extention, unification and peace. KCI Citation Count: 1